European Working Group on Clinical Cell Analysis: Consensus Protocol for the Flow Cytometric Characterisation of Platelet Function - Schmitz, Gerd; Rothe, Gregor; Ruf, Andreas; Barlage, Stefan; Tschöpe, Diethelm; Clemetson, Kenneth J.; Goodall, Alison H.; Michelson, Alan D.; Nurden, Alan T.; Shankey, Vincent T.; for the European Working Group on Clinical Cell Analysis (Thrombosis and Haemostasis, 1998)
An increased or disturbed activation and aggregation of platelets plays a major role in the pathophysiology of thrombosis and haemostasis and is related to cardiovascular disease processes. In addition to qualitative disturbances of platelet function, changes in thrombopoiesis or an increased elimination of platelets, (e. g., in autoimmune thrombocytopenia), are also of major clinical relevance. Flow cytometry is increasingly used for the specific characterisation of phenotypic alterations of platelets which are related to cellular activation, haemostatic function and to maturation of precursor cells. These new techniques also allow the study of the in vitro response of platelets to stimuli and the modification thereof under platelet-targeted therapy as well as the characterisation of platelet-specific antibodies. In this protocol, specific flow cytometric techniques for platelet analysis are recommended based on a description of the current state of flow cytometric methodology. These recommendations are an attempt to promote the use of these new techniques which are at present broadly evaluated for diagnostic purposes. Furthermore, the definition of the still open questions primarily related to the technical details of the method should help to promote the multi-center evaluation of procedures with the goal to finally develop standardized operation procedures as the basis of interlaboratory reproducibility when applied to diagnostic testing.